Agama pada Masa Dewasa - Ayilzi Putri; Bitri Hariani Lubis; Aslamiyah Abda Daulay; Ramadan Lubis; Alde Rizky Pratama Siregar; Muhammad Fachrezy Risdi; Muhammad Nuha Hidayat (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article aims to understand the role of religion in adulthood and how religious beliefs evolve with age. This research employs a literature review methodology by examining various sources related to the psychology of religion in adult individuals. The findings show that religion plays a significant role in providing emotional support, enhancing psychological well-being, and shaping life perspectives. Furthermore, religious commitment tends to increase with age, associated with the pursuit of meaning and life purpose. These findings suggest that religion can be a substantial source of mental strength for adults.